Sleep endoscopy-directed management of Arnold-Chiari malformation: a child with persistent obstructive sleep apnea - Katwa, Umakanth (J Clin Sleep Med, 2020)
Arnold-Chiari malformations are structural defects in the base of the skull and cerebellum, when part of the cerebellar tonsils herniates through the foramen magnum into the upper spinal canal, compressing against the brainstem. This anatomical defect can be asymptomatic but often presents with symptoms such as headaches, stridor, dysphagia, and nystagmus. It also presents with a variety of sleep-related breathing disorders such as snoring, obstructive sleep apnea, central sleep apnea, bradypnea, and sleep hypoventilation. Sometimes these conditions can coexist in one patient. Although obstructive sleep apnea can be a manifestation of Arnold-Chiari malformation, identifying causality and the site of obstruction in these children can be a diagnostic challenge. We review the case of a 14-month-old male who presented with noisy breathing and obstructive sleep apnea diagnosed on sleep study that was refractory to initial upper airway surgery. Although a brain computed tomography scan done in the emergency room for altered mental status revealed a type 1 Arnold-Chiari malformation, and a flexible awake laryngoscopy was normal, subsequent drug-induced sleep endoscopy was helpful in justifying surgical decompression of the Arnold-Chiari malformation that resulted in complete resolution of the obstructive sleep apnea. CITATION: Katwa U, Sisniega C, McKeon M, Lee GS. Sleep endoscopy-directed management of Arnold-Chiari malformation: a child with persistent obstructive sleep apnea. J Clin Sleep Med. 2020;16(2):325–329.